ALTERNATIVE WORK ARRANGEMENTS AS DETERMINANTS OF PRODUCTIVITY IN THE NIGERIAN HEALTH INSTITUTIONS - Enemuo, Joy Ifeoma; Onyejiaku, Chinyere Catherine; Onuselogu, Odidi Chineze Onyekachi (International Journal of Psychosocial Rehabilitation, 2020)
This study empirically investigates the relationship between alternative work arrangements and productivity in the Nigerian health institutions. The descriptive survey design was adopted with a population of 7,936 health professionals drawn from10 health institutions that were purposively selected from the five states in the South East, Nigeria. A sample size of 1,020 was adopted. The closed-ended structured questionnaire was the instrument used to collect data from the respondents. Results showed that compress work weeks, telecommuting, flexi time, and job sharing have a positive relationship with productivity in the Nigerian health institutions. The study concluded that non-adherence by the management of the selected federal and state hospitals to work-life balance initiatives is the major challenge to employees' performance, retention, and the overall actualization of set goals in the Nigerian health institutions. Based on the key finding, the study recommended that the management of health institutions in Nigeria should effectively adopt alternative work arrangement in order to offer a family friendly atmosphere to attract and retain qualified employees for increase productivity